Analysis of Practical Methods of Early Detection of Scoliosis - Utami, Feryanda; Adyas, Atikah (Poltekkes Kemenkes Jakarta I, 2022)
Scoliosis screening in school is essential for early detection before the curve worsens. Many idiopathic scoliosis patients occur in women with an average age of 14 years. They seek treatment when the age has reached skeletal maturity, and abnormalities have interfered with daily activities. Spinal surgery tends to require high costs, ranging from tens of millions to hundreds of millions of rupiah. Knowledge related to the basics of scoliosis is vital for the community because it affects the proper treatment according to their condition. The role of the Orthotist is still lacking in conducting regular scoliosis screening. We use data by purposive sampling based on inclusion criteria in clinics and hospitals that have spinal workshops or treat scoliosis. The study was conducted at two scoliosis clinics in Jakarta and two in Bogor, with quantitative methods via questionnaires and qualitative methods via Forum Group Discussion (FGD). Factors that influence orthotics in conducting scoliosis screening in patients are a lack of orthotic knowledge about appropriate scoliosis screening methods, especially related to indicators of ignorance of the SOSORT Guideline, not knowing the need to screen six parts of the patient's body, knowing the function of ATR and Scoliometer but not knowing how to apply them, and lack of active participation between orthotist and doctors. Several recommendations can be taken to improve scoliosis screening methods. Also a need to increase scoliosis screening knowledge, maximize scoliosis screening performance, and screen for scoliosis diagnosis by involving orthotics.